2015
DOI: 10.1021/jp510140a
|View full text |Cite
|
Sign up to set email alerts
|

H2O on Graphene/Ir(111): A Periodic Array of Frozen Droplets

Abstract: Scanning tunneling microscopy (STM) and thermal desorption spectroscopy (TDS) show that deposition of water molecules onto epitaxial graphene on Ir(111) leads to the formation of an extended and well ordered array of amorphous water clusters. We trace the evolution of this cluster phase as dependent on water exposure and deposition temperature. The formation of separated clusters is due to binding energy differences within the moiré superstructure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 41 publications
5
19
0
Order By: Relevance
“…2c. Such behaviour is consistent with the strongly hydrophobic behaviour previously seen on pristine graphene 13,35,36 and a similar behaviour has been observed for water on other metal-supported graphene systems 33,37 . The formation of islands provides the first indication that in this regime, water molecules must be able to diffuse freely over the graphene surface.…”
Section: Resultssupporting
confidence: 91%
“…2c. Such behaviour is consistent with the strongly hydrophobic behaviour previously seen on pristine graphene 13,35,36 and a similar behaviour has been observed for water on other metal-supported graphene systems 33,37 . The formation of islands provides the first indication that in this regime, water molecules must be able to diffuse freely over the graphene surface.…”
Section: Resultssupporting
confidence: 91%
“…16 In presence of less reactive adsorbates, such as H 2 O or small organic molecules, though, only physisorption was detected. 17,18 Following recent experimental work, 19 we analyze here the case of G deposited on a Ni(111) substrate, providing theoretical confirmation of enhanced G chemical reactivity upon CO adsorption. While the interaction between gaseous CO and free-standing G is controlled by weak long-range correlation effects, we find that, in presence of the Ni(111) substrate, two CO monomers can merge into chemisorbed ethylene dione (C 2 O 2 ).…”
mentioning
confidence: 94%
“…16 It was recently demonstrated that frozen water clusters of ∼1 nm size can be periodically arranged on graphene/Ir(111). 8 The arrangement of the water molecules inside the droplets is presumed to be amorphous, but their internal structure and phase has not been experimentally determined to this point. The moiré pattern of graphene on Ir(111) has a periodicity of 2.53 nm and provides an elegant way to decorate the surface with a high density of small nanoparticles with diameters up to 1.5 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Recent scientific work concerns water at various interfaces, where it forms patterns of molecular wetting layers. It was reported that water on surfaces can form half-dissociated adlayers, ordered structures as 2D stripes and patches, or self-assembled nanosized clusters . The interaction with a substrate is reported to lead to a preferential orientation of the water molecules, which hence has impact on micro- to macroscopic properties of water, for example, the flux through channels inside filtration membranes or other nanochannels .…”
Section: Introductionmentioning
confidence: 99%